An analysis of sugar-sweetened beverages elasticity of demand in Malaysia - Nor Asmat Ismail; Lynda Daud; Saidatulakmal Mohd; Intan Hashimah Mohd Hashim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sugar-Sweetened Beverage (SSB) tax is one of the measures undertaken by the government to improve the health index of Malaysians. This study intends to examine the SSB demand elasticity of low, medium, and high-income groups. Demand elasticity analysis is a technique for determining the impact of tax implementation on price increases. The study further examines SSB elasticity of demand based on age groups to explain obesity issues among children and diabetes among the elderly. In addition, this study examines the cross-elasticity of demand for SSB to investigate the effect of substitution. The Almost Ideal Demand System (AIDS) estimating model based on microdata from Malaysia Household Expenditure Survey, 2019, was used in this study. Results showed that households significantly reduced the intake of SSB when price increased. Price should accordingly be adopted by policymakers as an essential tool in controlling SSB consumption. However, consumers switch to SSB substitute to avoid the sugar tax. This study demonstrated the impact of SSB price changes on demand and the substitution effect of SSB which may guide pricing policy and the establishment of the SSB tax in Malaysia.